Sola Fide: Analisis Prinsip Iman Reformed sebagai Penjaga Identitas Orang Percaya Masa Kini (Jurnal Pendidikan Agama dan Teologi, 2025)
Sola fide is the main Reformed teaching that salvation is only obtained through faith alone, not through charity or good deeds. in the 16th century the practice of indulgences and the Catholic church's emphasis on good works gave rise to doubts in the faith, which later gave rise to the Reform Movement. In response, the reformers restored the principle of sola fide to protect believers in the Lord Jesus from doubts about their Faith. The aim of this research is to analyze the role of sola fide in strengthening believers' faith before reform skepticism, through a literature review of the writings of reformer figures. The results show that emphasizing God's sovereign grace, the sufficiency of faith for forgiveness of sins and assurance of salvation, and sola fide can strengthen believers' faith against attacks of skepticism. This understanding provides important insight for believers today about how to strengthen their faith in the face of increasing skepticism. Overall, this research shows the central role of the principle of sola fide in the history of Christian thought.